Complex reactions catalyzed by cytochrome P450 enzymes - Isin, Emre M.; Guengerich, F. Peter (Biochimica et biophysica acta, 2007)
Cytochrome P450 (P450) enzymes are some of the most versatile redox proteins known. The basic P450 reactions include C-hydroxylation, heteroatom oxygenation, heteroatom release (dealkylation), and epoxide formation. Mechanistic explanations for these reactions have been advanced. A number of more complex P450 reactions also occur, and these can be understood largely in the context of the basic chemical mechanisms and subsequent rearrangements. The list discussed here updates a 2001 review and includes chlorine oxygenation, aromatic dehalogenation, formation of diindole products, dimer formation via Diels–Alder reactions of products, ring coupling and also ring formation, reductive activation (e.g., aristolochic acid), ring contraction (piperidine nitroxide radical), oxidation of troglitazone, cleavage of amino oxazoles and a 1,2,4-oxadiazole ring, bioactivation of a dihydrobenzoxathiin, and oxidative aryl migration.